Peranan Pemerintah Dalam Memberantas Buta Aksara Al-Qur'an (Study Analisis di Kabupaten Sumenep) - Siti Aisyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
Miracles of the Qur'an as revealed to the Prophet Muhammad, it means that the scriptures contain "fabulosity" in all its aspects. Nevertheless, the significance of the miracle of the Qur'an is not solely for "fabulosity" weakens the human being in all and sundry, but i'jāz al-Qur'ān intent is to clarify the truth of the Qur'an and the Prophet (Prophet Muhammad) who brought it.